Answer:
[tex]g(x) = 2 (|x| - 3)[/tex]
Step-by-step explanation:
Given
[tex]f\left(x\right)=\mid x\mid[/tex]
Translation = 3 units down
Vertical stretch of 2 to give g(x)
Required
[tex]g\left(x\right)[/tex]
3 units down translation
A function is translated down as follows:
[tex]h(x) = f(x) - k[/tex]
Where k is the number of units.
So:
[tex]h(x) = f(x) - k[/tex]
[tex]h(x) = |x| - 3[/tex]
Vertical stretch of 2
A function is vertically stretched as follows;
[tex]g(x) = ah(x)[/tex]
Where a is the units stretched.
In this case:
[tex]a = 2[/tex]
So:
[tex]g(x) = ah(x)[/tex]
[tex]g(x) = 2 * (|x| - 3)[/tex]
[tex]g(x) = 2 (|x| - 3)[/tex]